Transformational, Transactional & Laissez-Faire Leadership Styles: A Gender Analysis - Sohail Imran Khan; Nabaz Nawzad Abdullah; Rohat Sheik Esmaeel Zada (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Male leaders are bound to show different features of transformational, transactional, and laissez-faire leadership. The study investigates to discover experimental proof on whether female leadership styles contrast or like male administration styles. The study intends to distinguish female leaders from male leaders on groundbreaking, conditional and free enterprise administration styles. The Multifactor Leadership Questionnaire, dependent on Full Range Leadership Development Theory, was utilized to decide authority styles. The results identify those female leaders have more groundbreaking characteristics (with an average mean of 2.87 as compared to 2.83 for males). However, it was also found that in transactional and laissez-faire styles of leadership, male leaders have an edge over female leader. The study highlights this characteristic supports them to overcome challenges when practicing their leadership styles. It’s also found to be important to fulfill women’s gender gaps and fulfilling their needs to show their actual roles adjusted to their sexual orientation positions. It is recommended that women leaders should concentrate on different aspects and parameters of leadership style